Peripandemic outcomes of infants treated for sentinel congenital heart diseases in England and Wales - Massimo Caputo; Christina Pagel; Sonya Crowe; John Nolan; Deborah A Lawlor; Qi Huang; Rodney CG Franklin; Kate L Brown; Ferran Espuny-Pujol (Open Heart)
Background Infants with congenital heart disease (CHD) are clinically vulnerable to cardiac deteriorations and intercurrent infections. We aimed to quantify the impact of health system disruptions during the COVID-19 pandemic, on their clinical outcomes and whether these differed by socioeconomic and ethnic subgroups.Methods In this population-based cohort study, we used linked electronic healthcare datasets from England and Wales to identify infants with nine sentinel CHDs born and undergoing intervention in 2018–2022. The outcomes of cardiac intervention timing, infant mortality and hospital care utilisation, were described by birth eras, and risk factors were explored using multivariable regression.Results Of 4900 included infants, 1545 (31.5%) were born prepandemic (reference), 1175 (24.0%) in the transition period, 1375 (28.0%) during restrictions and 810 (16.5%) postrestrictions. The casemix was hypoplastic left heart syndrome (195; 3.9%), functionally univentricular heart (180; 3.7%), transposition (610; 13.5%), pulmonary atresia (290; 5.9%), atrioventricular septal defect (590; 12.1%), tetralogy of Fallot (820; 16.7%), aortic stenosis (225; 4.6%), coarctation (740; 15.1%) and ventricular septal defect (1200; 24.5%).Compared with prepandemic, there was no evidence for delay in treatment procedures in transition, restrictions or postrestrictions eras. Infant mortality increased for those born in the transition period, adjusted OR 1.60 (95% CI 1.06, 2.42) p=0.01, but not in restrictions or postrestrictions. The days spent at home were similar with birth in transition and restrictions, but fewer for postrestrictions, adjusted days difference −2 (95% CI −4, 0), p=0.05.Outcomes did not vary by pandemic birth era according to social characteristics. There was higher infant mortality in the deprived versus non-deprived binary category (adjusted OR 1.56 (95% CI 1.11, 2.18), p=0.004) and there were fewer days spent at home for the most versus least deprived neighbourhood quintile (adjusted difference −4 (95% CI −6, –2), p<0.001).Conclusions Specialist care for infants with CHD during the pandemic, in terms of pathway procedure timing and healthcare contacts, was not compromised. Increased healthcare utilisation postpandemic and heath inequality based on socioeconomic status require further evaluation.